On Maximum Energy of Mechanical Systems Under Shock Disturbances - Dimitry V. Balandin (Shock and Vibration)
In this article, we develop a method for estimating the maximum energy of a mechanical system subjected to disturbances whose integral absolute value is bounded. The conditions for this estimate to be exact are found. The method is demonstrated by calculating the maximal displacement in a second-order nonlinear system.